Macronutrient contents of eggplant seeds with different ages and postharvest resting times - Aguilar, Ariel Santivañez [UNESP] (2020)
The seed nutritional status is of essential importance to seed storage capacity and vigor, especially for horticultural crops, such as the eggplant. Thus, this study aimed to evaluate the macronutrient contents in eggplant seeds with different ages and times after the fruit harvest. Twelve treatments were evaluated-four fruit ages (40, 50, 60 and 70 days after anthesis), and three periods of resting after the harvest of the fruits (PRAHF) (0, 10 and 20 days). The experiment was conducted in a pro-tected cultivating area. The dry biomass of 1000 eggplant seeds and contents of seed macronutrients were evaluated. The N concentration decreased with the increase of the fruit age, however, the PRAHF did not affect its content. The seed P content did not change with fruit age or PRAHF. For the seed K, Mg, S and Ca contents it was observed interaction between fruit age and PRAHF, and generally, the contents of these macronutrients decreased with fruit age and the PRAHF. The reductions in seed N, K, Ca and Mg contents correlate with the increase of the 1000 seeds dry mass, probably due to a dilution effect. The descending order of macronutrients contents in eggplant seeds is N>K>P>Mg>S>Ca.